High yielding nutmeg (Myristica fragrans Houtt.) varieties: a farmer-centric research approach to select superior trees: High yielding nutmeg Varieties - Miniraj, N; Vikram, H C; Nybe, E V; Philip, Manu (Journal of Spices and Aromatic Crops, 2023)
A comprehensive survey was conducted in the nutmeg-growing region of Kerala state to locate superior clones of nutmeg, by employing Participatory Varietal Selection (PVS) method. Twenty-nine superior accessions were identified through mother tree characterization for four consecutive years. The characterized clones were female and produced fruits ranging from 628 to 2250 tree-1 year-1, dry nut weight varied from 3.27 g to 15.37 g, and assorted dry mace weight varied from 0.35 g to 4.80 g. Genetic variability analysis revealed high heritability with high genetic advance as per se mean (dry mace weight 76.30%, dry kernel weight 71.37% and the number of fruits tree-1 73.24%) which signifies the advantage of simple selection method of breeding. Based on the economic importance of yield contributing characteristics, five superior clones out of twenty-nine mother trees evaluated have been released as KAU- farmer’s varieties. All the superior trees identified based on yield traits had appreciable quantities of volatile oil (1.63-12.25% in nut; 3.31-16.97% in mace), oleoresin (17.60-41.77% in nut; 13.00-30.50% in mace) and fixed oil (22.45-40.70% in nut) in their nuts and maces as well as myristicin, elemicin, safrole and sabinene in the volatile oils. The characteristic features of mother trees and released varieties are discussed in this paper, and further, these varieties are recommended for commercial cultivation under tropical moist, humid climate conditions.